PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) DENGAN APLIKASI CANVA UNTUK MENINGKATKAN PRESTASI BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN PESERTA DIDIK KELAS XII BDP 1 SMK NEGERI 1 NEGARA - Ni Kadek Nora Utarini (Widyadari : Jurnal Pendidikan, 2022)
This classroom action research aims to increase students’ achievement of entrepreneurship and creative product lesson by applying learning model Project Based Learning (PjBL). This research was conducted in class XII BDR SMK Negeri 1 Negara at second term in academic year 2021/2022 to 33 students. The research’s result shows at cycle 1, the mean score is 74,30 which is categorized good and mastery of learning outcomes achieve 72,73% classically. Meanwhile, at cycle 2, the mean score results 82,42 which is categorized good and mastery of learning outcomes achieve 96,97% classically. The result shows that the applying of Project Based Learnng model using Canva application can increase students’ achievement of entrepreneurship and creative product lesson at class XII BDR 1 SMK Negeri 1 Negara at second term in academic year 2021/2022